2015
DOI: 10.2987/14-6469r
|View full text |Cite
|
Sign up to set email alerts
|

Mosquitoes and the Environment in Nile Delta Villages with Previous Rift Valley Fever Activity

Abstract: The use of content from this health information product for all non-commercial education, training and information purposes is encouraged, including translation, quotation and reproduction, in any medium, but the content must not be changed and full acknowledgement of the source must be clearly stated. A copy of any resulting product with such content should be sent to TDR,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 17 publications
1
4
0
Order By: Relevance
“…The study showed that, Cx. pipiens is the most abundant species (71.2%) as compared with the other collected species, this indicated by other studies in other areas throughout Egypt (Hoogstraal et al, 1979Zayed 1989and Zayed et al, 2015. Cx antennatus was the 2 nd collected mosquito species fed mainly on human 100% from indoor as mixed blood and 10% as single blood meal, as well as cow blood 66.6% because of that this species act as a secondary vector of filariasis and in arbovirus transmission (Darwish and Hoogstraal, 1981, Zayed 1989and Zayed et al, 2015.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…The study showed that, Cx. pipiens is the most abundant species (71.2%) as compared with the other collected species, this indicated by other studies in other areas throughout Egypt (Hoogstraal et al, 1979Zayed 1989and Zayed et al, 2015. Cx antennatus was the 2 nd collected mosquito species fed mainly on human 100% from indoor as mixed blood and 10% as single blood meal, as well as cow blood 66.6% because of that this species act as a secondary vector of filariasis and in arbovirus transmission (Darwish and Hoogstraal, 1981, Zayed 1989and Zayed et al, 2015.…”
Section: Discussionsupporting
confidence: 69%
“…This study and most studies have shown that, Cx. pipiens is the most abundant species in other areas throughout Egypt (Hoogstraal et al, 1979 andZayed et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…pipiens density. Zayed and collaborators [ 17 ] demonstrated that in the areas where the seasonal flooding of the Nile Delta occurred, the population of vectors changed significantly, mainly in late summer-early fall.…”
Section: Discussionmentioning
confidence: 99%
“…Culex pipiens has been traditionally considered the main vector of RVFV in Egypt [ 16 ], and recent entomological studies seem to confirm that [ 17 ]. In fact the competence of Egyptian Cx .…”
Section: Methodsmentioning
confidence: 99%
“…Main vectors for the RVFV transmission in Egypt are mosquitos of genus Culex [40]. In 2009 Ramadan [27] collected these mosquitos from Dakahlia governorate and found 11.1% positive encompassing 806 mosquitos in 13 pools which indicates virus maintenance in the country.…”
Section: Discussionmentioning
confidence: 99%